A Novel Self-Micro-Emulsifying Delivery System Enhances Enrichment of Eicosapentaenoic Acid and Docosahexaenoic Acid after Single and Repeated Dosing in Healthy Adults in a Randomized Trial - West, Annette L; Kindberg, Grete Mørk; Hustvedt, Svein Olaf; Calder, Philip C (The Journal of nutrition, 2018)
A self-micro-emulsifying delivery system (SMEDS) promotes spontaneous emulsification of omega-3 (n–3) ethyl esters (EEs) into microdroplets in the stomach. The objective was to compare the effect of SMEDS preparations of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) EEs with standard EEs on EPA and DHA concentrations in the bloodstream after a single dose and repeated daily dosing. Eighty healthy subjects aged 18–65 y were randomly assigned to SMEDS-EPA or EE-EPA (both providing more EPA than DHA) or SMEDS-DHA or EE-DHA (both providing more DHA than EPA). They consumed a single dose (1.23–1.33 g EPA+DHA) without a meal, and EPA and DHA were measured in plasma over the following 24 h. Participants continued to take a single dose each morning before breakfast for 12 wk. EPA and DHA were measured in fasting plasma, mononuclear cells (MNCs), and RBCs. EPA and DHA were higher in plasma in the 24 h after a single dose of SMEDS-EPA or SMEDS-DHA than after consuming the comparator EE (P < 0.001 for both). Compared with the EE form, repeated daily dosing of the SMEDS formulations for 12 wk resulted in higher concentrations of EPA and DHA in plasma (P = 0.086 and 0.005, respectively), MNCs (P < 0.001 and 0.020, respectively), and RBCs (both P < 0.001). The omega-3 index increased over 12 wk from 5.1 ± 0.9 to 7.9 ± 0.9 in the SMEDS-EPA group, from 5.3 ± 1.1 to 9.0 ± 1.2 in the SMEDS-DHA group, from 4.8 ± 0.8 to 6.4 ± 0.9 in the EE-EPA group, and from 5.2 ± 0.9 to 7.2 ± 1.0 in the EE-DHA group (all P < 0.001). The omega-3 index was higher with SMEDS than with the comparator EE at 12 wk (both P < 0.001). Compared with standard EEs, a SMEDS results in greater incorporation of EPA and DHA into blood pools after a single dose and with repeated daily dosing in healthy adults. A SMEDS enhances delivery of bioactive ω-3 fatty acids. This trial was registered at www.isrctn.com as ISRCTN96459690.